Salt transport in soil profiles with application to irrigation return flow: the dissolution and transport of gypsum in soils - Glas, Tjaart Kornelis, author; McWhorter, David B., author; Environmental Resources Center, Colorado State University, publisher (Colorado State University. Libraries, 1976)
Experimental information on the dissolution of gypsum and the subsequent transport of the dissolved species in a soil-water system was obtained by measuring the calcium concentration in the solution phase as a function of time at different positions in columns filled with a soil-gypsum mixture that were leached with distilled water. These gypsum leaching experiments were performed with two different soils for a range of flow rates of the solution phase, solution contents and particle sizes of the gypsum material. The measured concentration-time curves were compared with results from two models, the first based on equilibrium chemical principles and the mixing cell concept and a second based on the one-dimensional convection-dispersion equation combined with a first-order kinetic rate equation describing the gypsum dissolution process. The formulation of the rate equation was based on the hypothesis that the rate of dissolution was proportional to the product of the saturation deficit and a function of the mass of gypsum present in the system. The equations in the kinetic model were solved numerically and a graphical and an optimization procedure were used to determine those values of the kinetic parameters for which the best possible agreement was obtained between the measured concentration-time curves and curves calculated from the kinetic model. It was concluded from the comparison between the experimental data, the mixing cell model and the kinetic model that the dissolution reaction of the gypsum was time dependent and was not controlled by the solubility product relationship, as assumed in the mixing cell model. The qualitative agreement between the kinetic model and the experimental results seems to support the hypothesis used in the formulation of the rate equation.
Submitted to Office of Water Research and Technology.
January 1976.
Keywords: Soils -- Leaching -- Mathematical models; Gypsum